INNOVATIVE WORK BEHAVIOR IN HOSPITALITY INDUSTRY: THE ROLE OF PSYCHOLOGICAL EMPOWERMENT AND WORK ENGAGEMENT - Suprapto, Widjojo; Williamsto, Angeline Putri; Palumian, Yonathan (Program Studi Manajemen Fakultas Ekonomi Universitas Siliwangi, 2024)
ABSTRACTThe purpose of this research is to explore how innovative work behavior (IWB) is constructed in a hospitality industry. Hospitality industry is one of highly standardized operating procedure industries. SOP often leaves less room for improvisation and innovation because every activity is standardized and evaluated based on the SOP. However, customers demand highly customized services that often need the creativity of the employees to meet the customers’ expectations. Therefore, this study is examining the influence of psychological empowerment and work engagement on IWB among the hotel employees. As quantitative research, the data were gathered using questionnaires which were distributed to 250 respondents, with 205 valid questionnaires. The respondents were the employees of three-to-five-star hotels who had been working for at least one year. Then, the collected data were processed and analyzed with the help of smartPLS software. This study finds that psychological empowerment does not influence significantly on IWB. However, work engagement influences significantly on IWB, and work engagement also mediates psychological empowerment and IWB.Keywords: innovative work behavior; psychological empowerment; work engagement; hotel management.ABSTRAKTujuan penelitian ini adalah mengeksplorasi bagaimana perilaku kerja inovatif (IWB) terbentuk di industri perhotelan. Industri perhotelan merupakan salah satu industri dengan prosedur operasi yang sangat terstandarisasi. SOP seringkali memberikan sedikit ruang untuk improvisasi dan inovasi karena setiap kegiatan distandarisasi dan dievaluasi berdasarkan SOP. Namun, pelanggan menuntut layanan yang sangat disesuaikan dengan keinginan mereka sehingga seringkali membutuhkan kreativitas karyawan untuk memenuhi harapan pelanggan. Oleh karena itu, penelitian ini menguji pengaruh pemberdayaan psikologis terhadap IWB melalui work engagement pada karyawan hotel. Sebagai penelitian kuantitatif, pengumpulan data dilakukan dengan menggunakan kuesioner yang disebarkan kepada 250 responden, dengan 205 kuesioner yang valid. Respondennya adalah karyawan hotel bintang tiga sampai lima yang telah bekerja minimal satu tahun. Kemudian data yang terkumpul diolah dan dianalisis dengan bantuan software smartPLS. Penelitian ini menemukan bahwa pemberdayaan psikologis tidak mempunyai pengaruh yang signifikan terhadap IWB. Namun work engagement mempunyai pengaruh yang signifikan terhadap IWB. work engagement juga berperan sebagai variabel intervening antara pemberdayaan psikologis dan IWB.Kata Kunci: innovative work behavior; psychological empowerment; work engagement; hotel management.